Selected Methods for the Chemical Phosphorylation and Thiophosphorylation of Phenols. Issue 2 (10th January 2018) - Kozak, Witold; Rachon, Janusz; Daśko, Mateusz; Demkowicz, Sebastian
Abstract: This Focus Review gathers together a selection of methods for the chemical phosphorylation of phenols that employ three‐ and four‐coordinate phosphorus compounds. Phosphorylated scaffolds can exhibit enhanced properties compared to their non‐phosphorylated analogues, such as increased biological activity and increased/decreased solubility; as such, phosphorus compounds have gained more and more interest in organic and medicinal chemistry. Phosphate esters are valuable intermediates in drug synthesis and, from this point of view, a knowledge of effective and selective methods for chemical phosphorylation is essential. Furthermore, phosphates form the basis of a large number of herbicides, insecticides, and nerve agents and they can act as flame retardants and plasticizers to protect or enhance the properties of various materials, such as textiles, furniture, or plastics. Abstract : I′ll have a P please Bob : This Focus Review discusses a selection of methods for the chemical phosphorylation of phenols by using three‐ and four‐coordinate phosphorus compounds.